Cdk5 knocking out mediated by CRISPR-Cas9 genome editing for PD-L1 attenuation and enhanced antitumor immunity - Deng, Huan (Acta Pharm Sin B, 2020)
Blocking the programmed death-ligand 1 (PD-L1) on tumor cells with monoclonal antibody therapy has emerged as powerful weapon in cancer immunotherapy. However, only a minority of patients presented immune responses in clinical trials. To develop an alternative treatment method based on immune checkpoint blockade, we designed a novel and efficient CRISPR-Cas9 genome editing system delivered by cationic copolymer aPBAE to downregulate PD-L1 expression on tumor cells via specifically knocking out Cyclin-dependent kinase 5 (Cdk5) gene in vivo. The expression of PD-L1 on tumor cells was significantly attenuated by knocking out Cdk5, leading to effective tumor growth inhibition in murine melanoma and lung metastasis suppression in triple-negative breast cancer. Importantly, we demonstrated that aPBAE/Cas9-Cdk5 treatment elicited strong T cell-mediated immune responses in tumor microenvironment that the population of CD8(+) T cells was significantly increased while regulatory T cells (Tregs) was decreased. It may be the first case to exhibit direct in vivo PD-L1 downregulation via CRISPR-Cas9 genome editing technology for cancer therapy. It will provide promising strategy for preclinical antitumor treatment through the combination of nanotechnology and genome engineering.